Innovative Videoscribe: Improving Science Learning Outcomes for Fourth Grade of Elementary School Students Through Character-Based Learning Media - Aprilianita, Kadek Ayu; Yudiana, Kadek (Indonesian Values and Character Education Journal, 2024)
The use of learning media is important in the learning process because it helps students understand the subject matter and stimulates students' attention and enthusiasm for learning. This research aims to describe the design and development of character education-based learning media in grade IV elementary school science subjects which have been tested for validity. This development research uses the ADDIE model, but is limited to the development stage due to limited time, situation and resources. The trial subjects included content experts, media experts, 2 design experts, 2 practitioners, and 18 grade IV students who participated in individual and small group trials. Data collection was carried out using a questionnaire in the form of a four scale instrument given to test subjects. Research data was analyzed using an average to determine the validity score of the media being developed. The results of the validity of learning media from the assessment of content experts, media experts, design experts and practitioners obtained very good qualifications. Individual and small group trials also demonstrated excellent qualifications. Based on this analysis, character education-based learning media in grade IV elementary school science subjects was declared valid and suitable for use in learning. This learning media is also a valuable resource and encourages teacher professionalism in teaching character values along with science material.